Lipid Oxidation at the Crossroads: Oxidative Stress and Neurodegeneration Explored in Caenorhabditis elegans - Julia Tortajada-Pérez; Andrea del Valle Carranza; Cristina Trujillo-del Río; Mar Collado-Pérez; José María Millán; Gema García-García; Rafael Pascual Vázquez-Manrique (Antioxidants)
Lipid metabolism plays a critical role in maintaining cellular integrity, especially within the nervous system, where lipids support neuronal structure, function, and synaptic plasticity. However, this essential metabolic pathway is highly susceptible to oxidative stress, which can lead to lipid peroxidation, a damaging process induced by reactive oxygen species. Lipid peroxidation generates by-products that disrupt many cellular functions, with a strong impact on proteostasis. In this review, we explore the role of lipid oxidation in protein folding and its associated pathological implications, with a particular focus on findings in neurodegeneration from Caenorhabditis elegans studies, an animal model that remains underutilized. Additionally, we highlight the effectiveness of different methodologies applied in this nematode to deepen our understanding of this intricate process. In the nervous system of any animal, including mammals and invertebrates, lipid oxidation can disturb the delicate balance of cellular homeostasis, leading to oxidative stress, the build-up of toxic by-products, and protein misfolding, key factors in neurodegenerative diseases. This disruption contributes to the pathogenesis of neurodegenerative disorders such as Alzheimer’s, Parkinson’s, or Huntington’s disease. The findings from Caenorhabditis elegans studies offer valuable insights into these complex processes and highlight potential avenues for developing targeted therapies to mitigate neurodegenerative disease progression.